Modelo sintético para estandarizar el índice de potencial turístico: Un enfoque basado en el concepto de distancia; Synthetic model for standardizing the tourism potential index: A distance-based approach - Eddy Soria Leyva; Jorge Luis Mari\~no Vivar; Félix Díaz-Pompa; Dayana Parra Parra; Yeilan Ivette González Odio (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– The assessment of tourism potential allows delimiting the attractiveness of tourism destinations, constituting the basis for the design of tourism products and experiences. To date, several studies have been conducted to measure destination attractiveness from a synthetic approach. However, there are still drawbacks to be overcome, such as the non-standardization of data and the modeling of static determinants, which presupposes a disadvantage when facing new research schemes immersed in big data. The present research aims to develop a generalized model for assessing destination attractiveness and standardizing the quantification of tourism potential, through the development of a flexible, standardized and bounded synthetic index, which will be useful for tourism agents, tourism planning and decision making. An application of the proposed model was carried out in the historic center of Santiago de Cuba concluding that this destination has a high tourism potential.
Keywords: O21; Z32; C65; C83; C02; 330; Tourism potential; tourism potential index; destination attractiveness; distance; data normalization